A mathematical computer model for estimating phase weight/ atomic fractions for Iron alags’ system (SiO2-Al203-CaO-MgO) at subsolidus temperatures - YELKENCİ, AHMET TANJU; ERKMEN, ZİYA ENGİN (My University, 2023)
In this study, the 3 dimensional description of the quaternary subsolidus slag system alumina-silica-calcia-magnesia is evaluated using Mathematica programming based on previous experimental research data. The lever rule in the tetrahedra is then applied for a given arbitrary liquid composition A% + %B + %C + %D = 100 in order to calculate the solid phases present (neglecting solid solutions) with their relative proportions after the solidification is completed. A novel transformation and algorithm are then developed using simple geometry and MathLab programming which can also be used for other subsolidus systems in case appropriate data are provided.
Keywords: Metalurji ve Malzeme Mühendisliği; Malzeme Bilimi ve Mühendisliği; Diğer; Mühendislik ve Teknoloji; Metallurgical and Materials Engineering; Material science and engineering; Other; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Malzeme Bilimi; METALURJİ VE METALURJİ MÜHENDİSLİĞİ; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE; METALLURGY & METALLURGICAL ENGINEERING; iron steel slag; mathematical model; quaternary system; subsolidus equilibrium